KAJIAN KETERSEDIAAN AIR BAKU WILAYAH PERBATASAN ARUK – SAJINGAN BESAR STUDI KASUS DESA SEBUNGA KECAMATAN SAJINGAN BESAR KABUPATEN SAMBAS - Reza Wahyudi; Wahyu Prayitno; Muhammad Elifant Yuggotomo (Jurusan Teknik Lingkungan, FTM, Universitas Pembangunan Nasional “Veteran” Yogyakarta, 2020)
One of the Indonesian government's policies to support border areas is the supply of raw water in border areas. This was carried out by an order to support the development and development program of the Aruk - Sajingan Besar border area, which was intended to accelerate development in the border area which has been known as a backward area. To support the development and development of the Aruk border region, various attempts have been made by the central government and the provincial government of West Kalimantan. This research is one of the efforts to support the government program by examining the availability of raw water in the Aruk-Sajingan Besar border area. Based on the results of the hydrological study at the study site, the mainstay discharge of raw water reaches 0.5 - 2 m3 / sec with a large evapotranspiration of 3-4 mm / day. In addition, this study also projects water needs for the next 25 years, these results are compared with the availability of raw water so that it can be concluded that up to 2045 the people of Sebunga Village, Sajingan Besar District, Sambas Regency, water needs can be met.